Clinical researchDecreased kidney function as a risk factor for cardiovascular events in subjects with metabolic syndrome – a pilot study - Barylski, Marcin; Banach, Maciej; Mikhailidis, Dimitri; Pawlicki, Lucjan; Kowalski, Jan (Archives of Medical Science, 2008)
Introduction: Chronic kidney disease (CKD) is an independent risk factor for cardiovascular events. The aim of the study was to estimate the level of kidney function in subjects with metabolic syndrome (MetS). Material and methods: The study included 50 subjects (26 males and 24 females) with MetS (diagnosed on the basis of NCEP ATP III criteria) aged 56±12 years and 25 healthy subjects (13 males and 12 females) aged 54±13 years. Glomerular filtration rates (GFR) were estimated using the Cockroft-Gault (CG) and the Modification of Diet in Renal Disease (MDRD) formulas. An estimated GFR (eGFR) <60 ml/min/1.73 m 2 was defined as a risk factor for cardiovascular events. Results: An eGFR <60 ml/min/1.73 m 2 was observed in 5 MetS subjects (10%) (using the CG formula) and in 15 subjects (30%) (using the MDRD formula). Among healthy subjects, an eGFR <60 ml/min/1.73 m 2 was observed in 2 subjects (8%) (using either the CG or MDRD formulas). Conclusions: Because most patients with MetS are obese, the estimation of eGFR using the MDRD formula, compared with the CG formula, may be more representative. There is also a relationship between the eGFR value calculated with the MDRD formula and the level of triglycerides (TG) in patients with MetS. The decreased MDRD eGFR seen in 30% of patients with MetS may be related to impaired endothelial function and might be connected with the risk factors which are components of MetS.